Diagnostic Value of Mid Regional Proadrenomedullin as a Sepsis Biomarker in Pediatric Patients with Cancer-Related Chemotherapy - Joko Susanto; Muhammad Robiul Fuadi; Mia Ratwita Andarsini (Indian Journal of Forensic Medicine & Toxicology, 2022)
The aim of this study was to analyze the diagnostic value of mid regional proadrenomedullin as a sepsisbiomarker in pediatric patients with cancer-related chemotherapy. This cross-sectional observationalstudy was located in General Hospital Dr. Soetomo Surabaya from September until December 2020.International Pediatric Sepsis Consensus Conference criteria was used to define sepsis term on 2 studygroups. Serum mid regional proadrenomedullin has been drawn from 60 subjects (41 in-ward pediatricpatients) and measured on sandwich enzyme-linked immunosorbent assay from Elabscience® HumanMid Regional Proadrenomedullin. Humareader Single Plus® was used to measure the optical density.ROC analysis was used to find out cut off value, sensitivity, specificity, positive predictive value, negativepredictive value, negative likelihood ratio, positive likelihood ratio, and accuracy, respectively. Statisticsdeclared significant if p<0.05 (95% CI). Between groups, temperature and heart rate were statisticallydifferent (p<0.001; 95% CI). The median difference of mid regional proadrenomedullin between groupswas significant (p<0.05; 95% CI). Cut off value 2,88 nmol/L, sensitivity 60.0%, specificity 56.67%,positive predictive value 58.06%, negative predictive value 58.62%, positive likelihood ratio 1.38,negative likelihood ratio 0.71 and diagnostic accuracy 59.33% was obtained while area under curvewas 0.707, respectively. Sepsis in children with cancer –related chemotherapy has not well diagnosedby serum mid regional proadrenomedullin.